IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) KAMPUNG BUMI SAHAJA DISTRIK YAPSI KABUPATEN JAYAPURA - Bunga Umaiyah Pratiwi; Yosephina Ohoiwutun (JURNAL KEBIJAKAN PUBLIK, 2023)
This study aims to examine the Implementation of the ADD Program Policy in Jayapura Regency, precisely in Kampung Bumi Sahaja and to analyze the supporting and inhibiting determinant factors. This study used a qualitative approach with descriptive analysis. Data were obtained through observation, documentation and in-depth interviews with informants consisting of various elements of society. Data analysis includes the stages of data reduction, data presentation, data verification and drawing conclusions. The results showed that the implementation of the village fund program implementation policy in Jayapura district, precisely in Kampung Bumi Sahaja, involved various elements of the community and government, infrastructure development was appropriate because it had been felt by the community and in terms of decision making, the opinions of local community leaders were taken into consideration by government. Furthermore, the community hopes that in the future the allocation of village funds should be prioritized for development activities that can revive the local community's economy and are in accordance with the vision and mission of Jayapura Regency